EFEKTIFITAS PERAN KEPALA DESA DALAM MEMBANGUN HARMONISASIMASYARAKAT GUNA MENINGKATKAN PARTISIPASI DALAM PEMBANGUNAN - Farida Hanum; Bangga Putra Aldo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2017)
This study aims to analyze the effectiveness of the role of Wonokoyo village head in building community harmonization to increase participation in development. This study uses a quantitative method with a descriptive approach, by analyzing the effectiveness of the role of the village head in building community harmonization, whether in the reality of the role of village head in governance and community harmonization can be done effectively or not. To obtain these data, the researcher will conduct interviews with the parties involved in depth so that later the actual facts can be revealed. The theoretical contribution of this research is to add a variant of the analysis of leadership in the dynamics of diverse rural communities. The analysis of the role of the village head in building harmonization of the community is important to ensure that the service is at the ideal point or not.